Pengaruh Content Marketing, Influencer Marketing dan Electronic Word of Mouth terhadap Purchase Decision produk House of Smith - Rifaldi, Moch Fikri; Dedy Ansari Harahap; Mochamad Malik Akbar Rohandi (UNISBA Press, 2024)
Abstract. With the increasing usage of social media among the community, coupled with the advancements in technology, it has led to a boost in digital marketing innovations adopted by every brand, including House of Smith. This has resulted in the growth of innovative approaches in digital marketing on social media, one of which is to understand the implementation of content marketing, Influencer marketing, and electronic word of mouth on purchase decisions. The aim of this research is to investigate the influence of content marketing, Influencer marketing, and electronic word of mouth on the purchase decision of House of Smith products in Bandung city. This research belongs to the type of descriptive and verification research with quantitative methods. The sampling technique used is non-probability sampling, namely purposive sampling. The population in this research consists of consumers who have made purchases of House of Smith products more than once, aged between 15 to 29 years old, and residing in the city of Bandung. The sample used in the study amounted to 401 respondents .Analysis of the data used is descriptive and statistical analysis by using multiple linear regression analysis, F test and T test. The results of this research indicate that content marketing partially has a significant effect on purchasedecisions, Influencer marketing partially has a significant effect on purchasedecisions, and electronic word of mouth has a significant effect on purchasedecisions. Furthermore, simultaneously, content marketing, Influencer marketing, and electronic word of mouth have a significant effect on purchase decisions. Abstrak. Dengan adanya pertumbuhan pengunaan media sosial dikalangan masyarakat dan disertai dengan perkembangan teknologi yang ada, hal ini dapat meningkatkan inovasi pemasaran digital yang di lakukan oleh setiap brand, yaitu House of Smith. Hal tersebut menyebabkan pertumbuhan inovasi di bidang pemasaran digital di media sosial, salah satunya untuk mengetahui penerapan content marketing, Influencer marketing dan electronic word of mouth terhadap purchase decision. Penelitian ini bertujuan untuk mengetahui pengaruh content marketing, Influencer marketing dan electronic word of mouth terhadap purchase decision produk House of Smith di Kota Bandung. Penelitian ini termasuk ke dalam jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang pernah melakukan pembelian produk House of Smith lebih dari satu kali dengan usia 15 -29 tahun yang berdomisili di Kota Bandung. Kemudian didapatkan sampel sebesar 401 orang. Analisis data yang digunakan adalah analisis deksriptif dan statistik yaitu dengan menggunakan analisis regresi linier berganda, uji F dan uji T.Hasil penelitian ini menunjukkan bahwa content marketing secara parsial berpengaruh signifikan terhadap purchase decision, Influencer marketing secara parsial berpengaruh signifikan terhadap purchase decision dan electronic word of mouth berpengaruh signifikan terhadap purchasedecision. Lalu secara simultan content marketing, Influencer marketing, dan electronic word of mouth berpengaruh signifikan terhadap purchase decision.